Profesionalisme guru dalam menghadapi tantangan pendidikan di era globalisasi - fadilah, fikri; Khasanah, Nur (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
The professionalism of an educator in the context of global education is not limited to the implementation of learning in the classroom, but also encompasses holistic education, nurturing, mentoring, and the formation of students' character, enabling them to prepare for and develop themselves as critical and creative human resources. Teachers are individuals worthy of respect due to their dedication and deep concern for the success of the education and learning process within the school environment. In the 21st-century global era, the role of teachers has a significant contribution in supporting students' development to achieve more meaningful life aspirations. In the following discussion, aspects of teacher professionalism, challenges faced by teachers, expectations of professionalism, development of professional attitudes, as well as strategies to enhance it will be elaborated.